A Pilot Study Examining the Experience of Veterinary Telehealth in an Underserved Population Through a University Program Integrating Veterinary Students - Lundahl, Lauren; Powell, Lauren; Reinhard, Chelsea L.; Healey, Eleni; Watson, Brittany (Frontiers in Veterinary Science, 2022)
Cost and transportation are two commonly cited barriers to accessing health care in both human and veterinary medicine within underserved communities. While human medicine has utilized telehealth as a means of breaking down this barrier, limited research exists to describe its use in veterinary medicine. The Pets for Life (PFL) program has partnered with the Penn Vet Shelter Medicine Program to provide veterinary appointments to clients, at no cost to the client, in underserved zip codes through virtual telehealth visits. These visits incorporated veterinary students as part of their clinical rotations through a service learning based model. Between January and August 2021, 31 PFL clients and nine veterinary students completed surveys to describe the role of telehealth in addressing barriers to accessing veterinary care, their perceptions of telehealth appointments, the human-animal bond, and changes in veterinary student empathy. PFL clients completed the survey immediately following their telehealth appointment, and veterinary students completed surveys prior to and following their participation in the PFL appointments during the rotation. Nearly 25% of clients reported that they would not have been able to secure transportation and 58% reported they would not have been able to afford an appointment at an in-person veterinary clinic. The population of clients who responded that cost was a significant barrier to accessing care did not entirely overlap with those who responded that transportation was a significant barrier to accessing care, indicating support for the use of telehealth in providing an alternative modality to address transportation challenges as a barrier to accessing veterinary care. Additional data suggests that both client and student experience was overwhelmingly positive, providing support for further service learning initiatives in veterinary student education. Further research is warranted to continue to assess the emerging role of telehealth in improving veterinary care for underserved communities.